Safety profile of musculoskeletal contrast-enhanced ultrasound with sulfur hexafluoride contrast agent - Fischer, Christian; Kunz, Pierre; Strauch, Marten; Weber, Marc-André; Doll, Julian (Therapeutics and clinical risk management, 2020)
Purpose: Muscle, bone and tendon regeneration depend on the microperfusion of the corresponding tissue which can be quantified with contrast-enhanced ultrasound (CEUS) using sulfur hexafluoride contrast agent (SonoVue (R)). This study investigated the incidence of adverse events (AEs) in musculoskeletal patients and gives an overview of musculoskeletal CEUS applications. Patients and Methods: Based on 13 studies in a standardized monocentric setting, a total of 2268 CEUS examinations in 764 patients were performed and AEs due to the administration of sulfur hexafluoride contrast agent were classified as either mild, moderate or severe. Results: No fatal events occurred. AEs were reported in three cases, of which only one was classified as severe and two as mild. The total rate of all AEs was 0.13% and 0.04% for severe AEs. Conclusion: The present analysis confirms the safety of musculoskeletal CEUS using sulfur hexafluoride contrast agent with a lower rate of AEs than that reported for other contrast agents even in elderly patients with concomitant diseases.